Analisis Grafik Karakteristik Sensitivitas Sensor MQ-135 untuk Menentukan Persamaan Hubungan antara ppm dan Rs/Ro - Ari Bangkit Sanjaya Umbu (Jurnal Teori dan Aplikasi Fisika, 2023)
Abstract. MQ-135 sensor is a sensor capable of detecting acetone, toluene, alcohol, carbon dioxide, ammonia, and carbon monoxide. This sensor has been widely used as the main component in gas-based research. Analysis of sensor sensitivity characteristics is the first step for researchers to do to obtain an equation for the relationship between ppm and Rs/Ro. However, in most studies only analyzing gas charts are the object of research. This causes other researchers to do their own analyses for different types of gas. Based on that problem, the authors performed a graphical analysis of the sensitivity characteristics of the MQ-135 sensor for acetone, toluene, alcohol, carbon dioxide, ammonia, and carbon monoxide gases. The coordinate points for these gases are obtained using the WebPlotDigitizer application and coordinate data were analyzed using power regression. Based on the analysis results, the relationship equation between ppm and Rs/Ro for acetone, toluene, alcohol, carbon dioxide, ammonia, and carbon monoxide gas is shown in equations 16, 17, 18, 19, 20, and 21 respectively.